The Success of B2C Mobile Commerce: Adoption factors and Value propositions for Companies - López-Catalán, Blanca; San Martín, Sonia; Jiménez, Nadia (Cuadernos de Estudios Empresariales, 2017)
The literature has extensively analysed the factors affecting the adoption of this shopping channel by consumers. However, literature has not deepened in the same way on the value propositions that the firm can incorporate into its offerings including mobile pone characteristics as a channel. In order to contribute to marketing literature, we have developed a comprehensive view that addresses the B2C relationship in mobile commerce. In this line, the aim of this study is to determine the value propositions based on mobile technology including the factors involved in the success of mobile commerce from the consumer ‘s point of view. To achieve this purpose, we used secondary information and did an extensive review of the literature to classify different proposition of value in the mobile commerce literature. As a result, this study includes several factors that favour the adoption of mobile commerce from the point of view of consumers and put a special emphasis on the offering of six types of value propositions on which companies interested in mobile selling can articulate their business to make consumers adopt this type of purchase finally.